Constructing prevention programmes with a Māori health service provider view. (3rd July 2017) - Gifford, H.; Cvitanovic, L.; Boulton, A.; Batten, L.
ABSTRACT: Mainstream approaches to chronic condition management and prevention inadequately address the needs of Māori, the Indigenous people of New Zealand. Māori health service providers (MHSPs) are uniquely placed to address the critical gap in the prevention of chronic conditions. In this paper, we report qualitative research findings investigating how prevention was being modelled, practiced and measured in selected MHSP settings. Results indicate barriers to achieving wellbeing through health service delivery. The dominant individualistic, medical conditions-focused discourse, along with responding to acute need, is a driver of service delivery norms.There are examples of shifts in organisational structure and delivery configurations that demonstrate that these norms are being challenged and reframed, in some form, by MHSPs. Consolidation of these approaches requires significant work and increased resources as well as a broader systems-level response that prioritises prevention.